Systematic Reviews in Educational Research Methodology, Perspectives and Application - Zawacki-Richter, Olaf; Kerres, Michael; Bedenlier, Svenja; Bond, Melissa; Buntins, Katja (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2020)
In this open access edited volume, international researchers of the field describe and discuss the systematic review method in its application to research in education. Alongside fundamental methodical considerations, reflections and practice examples are included and provide an introduction and overview on systematic reviews in education research. Contents Reflections on the Methodological Approach of Systematic Reviews Ethical Considerations of Conducting Systematic Reviews in Educational Research Teaching Systematic Review Conceptualizations and Measures of Student Engagement The Role of Social Goals in Academic Success Target Groups Researchers, instructors, and students in the field of education and related disciplines The Editors Prof. Dr. Olaf Zawacki-Richter, Professor of Educational Technology, Center for Open Education Research (COER), Faculty of Education and Social Science, Carl von Ossietzky University of Oldenburg, Germany. Prof. Dr. Michael Kerres, Professor of Educational Science / Learning Technology & Innovations, Learning Lab, University of Duisburg-Essen, Essen, Germany. Dr. Svenja Bedenlier, Research Associate, Center for Open Education Research (COER), Faculty of Education and Social Science, Carl von Ossietzky University of Oldenburg, Germany. Melissa Bond, Research Associate, Center for Open Education Research (COER), Faculty of Education and Social Science, Carl von Ossietzky University of Oldenburg, Germany. Katja Buntins, Research Associate, Learning Lab, University of Duisburg-Essen, Essen, Germany.